(untitled) (Psychology Travelogs, 2024)
The article is devoted to the problem of the development creativity and communication skills of future psychologists, which forms the basis for the formation of their sociocultural competence in the process of professional training. In the article, creativity is considered in two directions. The first direction assumes the presence of intellectual prerequisites for creativity, the second - a personal approach characterized by special attention to emotional and motivational factors.The results of an empirical study of the relationship between creativity and communicative abilities of students of higher education are described.The results of diagnostics of the level of development of creativity and communication skills of future psychologists were analyzed. It was found that more than half of the respondents have a high level of communication skills development and an average level of creativity development.Negative correlations were established between aggressive communication style and originality, dependent communication style, originality and flexibility.Established relationships between the criteria of creativity and communication skills make it possible to state the fact that they mutually reinforce each other. A high level of creativity helps psychologists find innovative approaches to solving client problems, and developed communication skills contribute to the effective transfer of these ideas. Established connections emphasize the importance of developing constructive communication strategies, independence and self-confidence to increase the level of creativity of future psychologists.The results of the empirical study indicate that the development of creativity and communication skills of future psychologists will help to cope more effectively with professional challenges, to be more flexible and adaptable to different situations of communication with clients.